Concrete for extreme conditions proceedings of the international conference held at the University of Dundee, Scotland, UK on 9-11 September 2002 - Dhir, Ravindra K.; McCarthy, Michael J. 1965-; Newlands, Moray D. (Thomas Telford, 2002)
There is no substitute for concrete that can be used on the same engineering scale. Its sustainability, exploitation and further development are necessary for a healthy economy and environment worldwide. Concrete must keep evolving to satisfy the increasing demands of all its users.